Education of Thinking as a Path to Virtue and Happiness in Qutadghu Bilig - Taşdelen, Vefa (Journal of History Culture and Art Research, 2020)
Education of Thinking as a Path to Virtue and Happiness in Qutadghu Bilig Abstract Thinking is one of the most distinguishing characteristics of humans. Man/woman can understand through thinking, find his/her way through thinking, and solve inherent problems after giving some thought. Any educational activity, regardless of its type, initially aims to train the ability of our thinking. Thus although there are relatively new definitions such as “education of thinking”, “philosophy with kids”, “critical and creative thinking skills” education of thinking is in reality as ancient as the roots of humanity. The reason activities such as knowing, understanding, living, and creating value collectively delineate man’s main mission on the earth. Scholars, philosophers, ethicists, scientists, and educators are those who contribute to the development of thinking ability. Currently, training of the mind within the frameset of goodness values, to create a culture of living and worldview, and eventually liberating and improving the person is among the key objectives of education of thinking. Education of thinking does not merely consist of philosophy or pedagogy; it is the combination of both. According to philosophical tradition, activity such as ‘education of thinking’ and ‘philosophy for children’ are structured related with philosophers Socrates, Plato, Aristotle, Rousseau, Kant, and Dewey. Through this approach, which enables reconstructing Western philosophers’ views with respect to ‘education of thinking’, ‘philosophy for children’ is similarly viable to reconstruct the works of Eastern philosophers. One of these works is Qutadghu Bilig written by Yousuf Khass Khajib. Qutadghu Bilig is an outstanding literary work that aims to educate thinking ability and discipline emotions, behaviours and personality through highlighted values. This work attempts to answer the question of how to make qut, a coincidental and luck-based condition, which means ‘gizmo, fate, fortune, happiness’ and represents a state of goodness of people who have a temporary existence. Qutadghu Bilig asks whether qut can become a permanent entity in human, social and political life and whether it is achievable at all. This literary work attributes the continuity of qut to virtues such as knowledge, justice, forgiveness, compassion, generosity, tenderness, patience and perseverance. To ensure the continuity of qut requires such a higher mental state and spiritual dignity. That is only viable through educating and activating one's thinking ability. Kutadgu Bilig’de Erdem ve Mutluluk Yolu Olarak Düşünme Eğitimi Öz Düşünme, insanın en ayırıcı vasıflarından biridir. İnsan, düşünerek anlar, düşünerek yolunu bulur, düşünerek sorunlarını çözer. Hangi eğitim faaliyeti olursa olsun, öncelikle düşünme yetisini eğitmeyi amaçlar. Bu nedenle “düşünme eğitimi”, “çocuklarla felsefe”, “eleştirel ve yaratıcı düşünme becerileri” gibi adlandırmalar nispeten yeni olsa da, düşünme eğitimi aslında insanın tarihi kadar eskidir. Bunun böyle olmasının nedeni, bilme, anlama, yaşama, değer üretme faaliyetlerinin insanın yeryüzündeki temel konumunu tanımlıyor olmasıdır. Bilgeler, filozoflar, ahlakçılar, bilim adamları ve eğitimciler, düşünme yetisinin terbiyesine katkıda bulunan kişilerdir. Bugün de zihnin, iyilik değerleri çerçevesinde, bir yaşama kültürü ve dünya görüşü doğuracak, nihayetinde bireyin otonomisini sağlayacak ve geliştirecek şekilde eğitilmesi, düşünme eğitiminin temel hedefleri arasındadır. Düşünme eğitimi salt felsefeden ya da salt pedagojiden oluşmaz; her ikisinden de oluşur. Felsefe geleneği açısından bakıldığında, “düşünme eğitimi”, “çocuklarla felsefe” gibi etkinliklerin Sokrates, Platon, Aristoteles, Rousseau, Kant, Dewey gibi filozoflara geri götürülerek yapılandırıldığı görülebilir. Söz konusu yaklaşım açısından nasıl ki Batılı filozofların görüşleri “düşünme eğitimi”, “çocuklar için felsefe” kapsamında yeniden okunup değerlendiriliyorsa aynı şekilde doğulu filozofların/bilgelerin eserleri de okunabilir. İşte bu eserlerden biri, Kutadgu Bilig’dir. 1069 yılında, Karahanlı devletinde “has haciblik” (halkın sorunlarıyla ilgilenen ve bu sorunlardan Hakanı haberdar eden kişi) görevinde bulunmuş olan Yusuf Has Hacib tarafından yazılan eser, öncelikle düşünme yetisini eğitmek, öne çıkardığı değerlerle duyguları, davranışları ve kişiliği terbiye etmek isteyen bir çalışma niteliğindedir. Söz konusu eser, rastlantısal ve şansa bağlı bir durum olan; “uğur, baht, talih, mutluluk, devlet” gibi anlamlara gelen ve gelip geçici bir varlık olan insanın yeryüzündeki iyilik hâlini ifade eden kut’u, birey, toplum ve devlet hayatında nasıl sürekli hâle getirebiliriz, bunun bir yolu var mıdır, sorusuna cevap arar ve kutun sürekliliğini, bilgi, adâlet, bağışlayıcılık, merhamet, cömertlik, yumuşak huyluluk, sabır, metanet gibi erdem değerlerinde bulur. Kut’u sürekli kılmak böyle bir zihin durumunu ve ruh yüceliğini gerektirir. Bu da ancak düşünme yetisini eğitmek ve etkin hâle getirmekle gerçekleşebilir.